1995
DOI: 10.1002/1097-0142(19950801)76:3<501::aid-cncr2820760322>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy treatment of patients with hepatic metastases from neuroendocrine tumors

Abstract: Background. Liver metastases from neuroendocrine tumors often present with disabling symptoms due to syndromes of hormonal excess. A locally destructive technique such as hepatic cryotherapy not only alleviates symptoms but may improve survival in this group of patients. Methods. Six patients with metastatic neuroendocrine tumors were treated with hepatic cryotherapy. Four patients were symptomatic and three of these had elevated tumor markers from ectopic hormone production. Results. All patients are alive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(30 citation statements)
references
References 26 publications
0
28
0
2
Order By: Relevance
“…During freeze/thaw cycles, intracellular and extracellular ice formation occurs in an area termed 'the iceball' leading to tumor destruction. Use of hepatic cryotherapy at laparotomy or laporoscopy surgery for patients with endocrine metastases has been used for a number of years (Cozzi et al 1995, Shafir et al 1996, Shapiro et al 1998, Seifert et al 1998, Duperier et al 2001, Sheen et al 2002, Tait et al 2002 and has demonstrated successful results in terms of symptom control and objective tumor responses (Cozzi et al 1995, Shapiro et al 1998, Seifert et al 1998. Cryotherapy is an important supplement to surgical resection and allows regional destruction to lesions not amenable to resection.…”
Section: Cryotherapymentioning
confidence: 99%
“…During freeze/thaw cycles, intracellular and extracellular ice formation occurs in an area termed 'the iceball' leading to tumor destruction. Use of hepatic cryotherapy at laparotomy or laporoscopy surgery for patients with endocrine metastases has been used for a number of years (Cozzi et al 1995, Shafir et al 1996, Shapiro et al 1998, Seifert et al 1998, Duperier et al 2001, Sheen et al 2002, Tait et al 2002 and has demonstrated successful results in terms of symptom control and objective tumor responses (Cozzi et al 1995, Shapiro et al 1998, Seifert et al 1998. Cryotherapy is an important supplement to surgical resection and allows regional destruction to lesions not amenable to resection.…”
Section: Cryotherapymentioning
confidence: 99%
“…With technological improvements in cryotherapy equipment and intraoperative ultrasound equipment, the technique has gained more widespread acceptance [3][4][5]. To the best of our knowledge, there has been one previous report of the use of cryotherapy to treat metastatic neuroendocrine tumors [6]. This report included three patients with carcinoid tumors, only one of which had carcinoid syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy offers the ability to treat multiple bilobar hepatic lesions that would not be amenable to surgical resection. It also offers the ability to alleviate symptoms by destroying hormone-producing tumor cells [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one report, cryosurgery was shown to be effective in alleviating the symptoms associated with hormonal secretion by neuroendocrine metastases. 111 Currently, cryosurgical ablation is considered an investigational form of therapy for the treatment of metastatic cancer. The efficacy of this approach, either in unresectable patients or as an alternative or adjuvant to resection, should be evaluated in the setting of formal clinical trials.…”
Section: Cryosurgery and Other Forms Of Local Hepatic Ablative Therapymentioning
confidence: 99%